Influence of Ethical Climate and Innovative Behavior of Administrators on Organizational Effectiveness - Hilot, Regina Mae (International Journal of Scientific Research and Management (IJSRM), 2022)
The primary objective of this study was to ascertain the major impact of administrators' ethical climate and innovative behavior on organizational effectiveness. The study used a correlational technique in a quantitative, non-experimental design. The responders were the 305 employees of Davao de Oro Province's Department of Public Works and Highways. The mean, Pearson-r, and regression were utilized to determine the study's findings. Additionally, questionnaires customized for ethical climate, innovative behavior, and organizational efficiency were used. The results indicate that the ethical climate is extremely high, the administrator's creative behavior is very strong, and the organizational development is overall very high. Further, the ethical climate is significantly correlated with organizational effectiveness. In the same way, innovative behavior has a significant relationship with organizational effectiveness. Meanwhile, in its singular capacity, the domain innovative behavior of administrators best influences organizational effectiveness. Moreover, ethical climate can influence organizational effectiveness but with the help of other variables. Likewise, this study has determined the importance of innovative behavior of administrators in achieving organizational effectiveness.